Psychic wear and social vulnerability of Zapotlenses women: A descriptive study - Saldaña-Orozco, Claudia; Carrión-García, María Ángeles; Gutiérrez-Strauss, Ana María; Hernández-Flores, Mónica Alejandra (Universidad y Salud, 2017)
Introduction: Numerous studies have documented the impact of psychosocial risks, and particularly the psychic wear on workers’ health. However, women in a situation of social vulnerability have not been the subject of exploration. Objective: To characterize the psychic wear in a sample of vulnerable women. Materials and methods: An exploratory, descriptive and correlational study was conducted. The dimension number 4 from the Battery for the study of the working conditions of psychosocial character was applied (CTCPS-MAC), which evaluates psychological wear and 3 particular factors (cognitive-emotional response; behavioral response and physiological response) at 99 Vulnerable women of Zapotlán el Grande. Results: A 75.8 % of the participants presented optimal conditions with ratings between good and very good, 24.2% between normal and harmful, which indicates that they require immediate assistance. The most affected factor was number 1 (cognitive-emotional response), 52,5% presented negative symptomatology. There were no significant associations between the sociodemographic variables studied and the psychic wear. Conclusions: The results allow to open doors for deeper investigations with the population studied in order to guarantee mental health and quality of life for women with social vulnerability in Zapotlán el Grande.